Factors Influencing Food Handlers' Knowledge and Hygiene Behavior at Street Food Vendors in East Surabaya: A Cross-sectional Study - Fadilatus sukma ika Noviarmi; Ratih Damayanti; Herman Bagus Dwicahyo; Mochammad Sholehhudin; Salsabila Al Firdausi; Nur Anisah Rahmawati; Shofiyatur Rohmah; Indah Lutfiya (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2026)
Introduction: Street food vendors play a significant role in providing ready-to-eat food in urban areas, including East Surabaya, which has hundreds of street food outlets. However, issues related to hygiene and sanitation practices among food vendors remain a significant challenge. This study aimed to examine the factors influencing the knowledge and hygiene practices of food handlers among street vendors in East Surabaya.Methods: This observational study used a cross-sectional approach and included 86 food handlers. Samples were selected using a purposive sampling technique with predetermined inclusion (location, age, willingness, and work period) and exclusion criteria (not active, health condition). Data were collected using a structured questionnaires. The independent variables were age, gender, and education, and the dependent variables were knowledge and behavior. Statistical analysis was performed using the chi-square test, and the Spearman test was used for ordinal data analysis.Results: The results showed that 68.6% of respondents exhibited inadequate hygiene behavior, a proportion that was particularly prominent among those aged ≤ 30 years (77.8%), males (83.3%), and high school graduates (79.3%). Respondents' knowledge varied by age, gender, and education. Strong knowledge was more prevalent among female respondents and those with higher levels of education. Significant relationships were identified between sex and education level with knowledge (p = 0.000 and p = 0.005), as well as between sex and hygiene behavior (p = 0.002).Conclusion: Female gender was the determinant for better knowledge and hygiene behavior, while higher education was the determinant of knowledge of food handlers. This indicates the need for more targeted educational interventions to improve hygiene practices among informal food handlers.